Sejarah Sosial Hukuman Peminum Khamr - Malik, Arif Jamaluddin (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: Penalty for a drinker can not be separated from the development and changes in society. As one of the many provisions of a criminal penalty, drinker should remain be punished. However, in practice, there are differences in accordance with the implementation of penalty for a drinker. It is about the amount and limit of the punishment given to a drinker. This is because al-Quran does not explicitely mention the legal sanctions for a drinker. In contrast to the punitive sanction for the variant of violations of a criminal penalty, such as fornication, adultery, and theft of the mentioned amount and limit of their sentence. The differences in the application of a criminal penalty for drinkers at the Prophetâs time time and after indicate that although the substantive criminal penalty should remain in force, but in the application might be heavier or at least equal as the former penalty. Those facts indicate that Islamic law is related to the changes and development of society. Thus, there is an interplay circumstance between Islamic law and the developments and changes in society, or in otherwise.Keywords: History, penalty, liquor, criminal penalty